Development of a Comprehensive Battery to Collect Social and Structural Determinants of Health (SSDOH) in Cognitively Normal or Very Mildly Impaired Persons. (6th April 2022) - Streitz, Marissa L.; Denny, Andrea; Xiong, Chengjie; McCue, Lena; Stites, Shana D.; Midgett, Sharnita; Mechanic-Hamilton, Dawn; Moulder, Krista L.; Morris, John C.; Balls-Berry, Joyce
Abstract : Introduction: Research addressing Alzheimer disease and related dementias must examine nonbiological factors influencing the risk for and expression of Alzheimer disease and related dementias. These factors address the interplay of cognition with lived experiences and social and structural determinants of health (SSDOH). However, coordinated measures of SSDOH are limited. Methods: The Knight Alzheimer Disease Research Center (ADRC) at Washington University in St. Louis developed and piloted a comprehensive battery to measure SSDOH. One hundred and twelve participants, very mildly cognitively impaired or unimpaired, enrolled in memory studies completed the electronic SSDOH battery. The Clinical Dementia Rating (CDR) determined the presence or absence of cognitive impairment. Results: Four domains demonstrated above acceptable intraclass correlation scores for test-retest reliability (≥0.70), including adverse childhood events, discrimination, social status, and early education. Twenty very mildly impaired participants completed the electronic pilot study. Conclusion: Our findings indicate that participants with early-stage symptomatic Alzheimer disease are able to participate in electronic SSDOH data collection. In collaboration with the University of Pennsylvania ADRC, we replaced/modified certain assessments to increase intraclass correlation. The resulting battery, Social and Structural Life-courses Influencing Aging and Dementia (SS-DIAD), can serve as a SSDOH collection tool and is currently utilized in cognitively impaired and unimpaired research participants at both ADRCs.